Drug Patent Monopoly During Covid-19 Outbreaks: How the Government Regulates this? - Devica Rully Masrur; Ogah Chinyere Constance (Faculty of Law, Universitas Negeri Semarang, 2023)
Health is an inherent human right constitutionally guaranteed, and during the Global Covid-19 Pandemic, the Indonesian government faced a delicate balance between safeguarding public health and complying with its obligations as a member of the WTO under the TRIPS Agreement, which mandates patent protection for medicines, medical devices, and vaccines, crucially needed during the pandemic. International and national laws have addressed these challenges through the TRIPs Protector Article, providing options for member states to take specific measures, such as Parallel Imports, Bolar Provisions, Compulsory Licenses, and Government Use of Patents. These solutions demonstrate that even in emergency situations, the rights of inventors can still be upheld while ensuring access to essential medicines for the public. In the case of Indonesia, the government employed the Government Use of Patents policy through Presidential Regulations Number 77 of 2020, Number 100 of 2021, and Number 101 of 2021, pertaining to Remdesivir and Favipiravir medicines, respectively. This approach, though involving compulsory acquisition, is time-limited, non-exclusive, and provides fair compensation to patent holders, reflecting a balanced and just approach to addressing the critical public health needs during the pandemic.